DIEL BEHAVIOR OF RARE EARTH ELEMENTS IN A MOUNTAIN STREAM WITH ACIDIC TO NEUTRAL PH - Gammons C.H.; Wood S.A.; Nimick D.A. (My University, 2005)
Diel (24-h) changes in concentrations of rare earth elements (REE) were investigated in Fisher Creek, a mountain stream in Montana that receives acid mine drainage in its headwaters. Three simultaneous 24-h samplings were conducted at an upstream station (pH = 3.3), an intermediate station (pH = 5.5), and a downstream station (pH = 6.8). The REE were found to behave conservatively at the two upstream stations. At the downstream station, REE partitioned into suspended particles to a degree that varied with the time of day, and concentrations of dissolved REE were 2.9- to 9.4-fold (190% to 830%) higher in the early morning vs. the late afternoon. The decrease in dissolved REE concentrations during the day coincided with a corresponding increase in the concentration of REE in suspended particles, such that diel changes in the total REE concentrations were relatively minor (27% to 55% increase at night). Across the lanthanide series, the heavy REE partitioned into the suspended solid phase to a greater extent than the light REE. Filtered samples from the downstream station showed a decrease in shale-normalized REE concentration across the lanthanide series, with positive anomalies at La and Gd, and a negative Eu anomaly. As the temperature of the creek increased in the afternoon, the slope of the REE profile steepened and the magnitude of the anomalies increased.